MACI - a new era? - Jacobi Matthias; Villa Vincent; Magnussen Robert A; Neyret Philippe (BMC, 2011)
Abstract Full thickness articular cartilage defects have limited regenerative potential and are a significant source of pain and loss of knee function. Numerous treatment options exist, each with their own advantages and drawbacks. The goal of this review is to provide an overview of the problem of cartilage injury, a brief description of current treatment options and outcomes, and a discussion of the current principles and technique of Matrix-induced Autologous Chondrocyte Implantation (MACI). While early results of MACI have been promising, there is currently insufficient comparative and long-term outcome data to demonstrate superiority of this technique over other methods for cartilage repair.